Analysis of anterior tibial subluxation to the femur at maximum extension in anterior cruciate ligament-deficient knees - Kyohei Nishida; Takehiko Matsushita; Daisuke Araki; Hiroshi Sasaki; Toshikazu Tanaka; Yuichi Hoshino; Noriyuki Kanzaki; Tomoyuki Matsumoto; Kouki Nagamune; Takahiro Niikura; Masahiro Kurosaka; Ryosuke Kuroda (Journal of Orthopaedic Surgery, 2019)
Purpose: The factors affecting anterior tibial subluxation (ATS) have not yet been well examined. To assess the factors affecting ATS in anterior cruciate ligament (ACL)-deficient knees. Methods: One hundred twenty-four patients with unilateral ACL injuries were included. True lateral views of the ACL-deficient knee and contralateral normal knee were obtained during maximum extension using fluoroscopy under general anesthesia, and ATS was calculated as the side-to-side difference in the tibial position relative to the femur. Patients were divided into four groups according to the time from injury to surgery. To identify the factors affecting ATS, the following possible factors were assessed: (1) the time from injury to surgery, (2) presence of a medial meniscal injury, and (3) posterior tibial slope angle. Results: There was a positive correlation between the ATS ratio and the time from injury to surgery ( r = 0.52). The ratio of the presence of a medial meniscus injury was significantly higher in patients who underwent anterior tibial subluxation reconstruction (ACL-R) more than 12 months after an injury than in other patients who underwent ACL-R within 12 months after an injury. The ATS ratio was significantly higher in patients with a medial meniscus injury than in those without a medial meniscus injury (5.6% vs. 4.1%). Conclusions: Our results suggested that ACL-R should be performed within 6 months after injury if surgeons prefer to avoid an increase in ATS in maximum knee extension and at the latest within 12 months to avoid medial meniscal injury at the time of ACL-R.